Lipoaspiração na Face/ Liposuction in Face - Lybio Martire Junior (Hospital de Clínicas de Itajubá, 2011)
O autor apresenta sua experiência na lipoaspiração da face demonstrando que a mesma pode ser realizada em qualquer parte da face, podendo ser feita como procedimento único ou associada a outras cirurgias estéticas da face. Expõe também os cuidados necessários para impedir complicações, tornar o procedimento inócuo e também aprimorar o resultado. Liposuction in Face The author presents his experience in liposuction on face demonstrating that the same can be accomplished in any part of the face, and can be performed as a single or combined with other surgeries. Exposes also the care required to prevent complications, making innocuous procedure and also improve the result.